2021
DOI: 10.3389/fpls.2021.657578
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Estimation of N Concentration in Wheat Organs for Assessing N Remobilization Under Different Irrigation Regimes

Abstract: Nitrogen (N) remobilization is a critical process that provides substantial N to winter wheat grains for improving yield productivity. Here, the remobilization of N from anthesis to maturity in two wheat cultivars under three irrigation regimes was measured and its relationship to organ N concentration was examined. Based on spectral data of organ powder samples, partial least squares regression (PLSR) models were calibrated to estimate N concentration (Nmass) and validated against laboratory-based measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Similarly, Santis et al. (2021) found that drought stress could lead to poor grain sets and yields, and Li et al. (2021) recorded low yields in plants subjected to low-level irrigation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Santis et al. (2021) found that drought stress could lead to poor grain sets and yields, and Li et al. (2021) recorded low yields in plants subjected to low-level irrigation.…”
Section: Discussionmentioning
confidence: 97%
“…adequate supply of water. Similarly, Santis et al (2021) found that drought stress could lead to poor grain sets and yields, and Li et al (2021) recorded low yields in plants subjected to lowlevel irrigation. However, it has previously been reported that a slight or moderate water deficit prior to the stem elongation stage and slight water deficit during the grain-filling stage did not significantly reduce grain yield, which lead to a significant water conservation (Meng et al, 2016).…”
Section: Effects Of Drought Stress On the Yield And The Mechanisms Wh...mentioning
confidence: 98%
See 1 more Smart Citation
“…The operation of nitrogen varies in different growth stages and different organs in crops (Ohyama Takuji, 2010). Studies have indicated that different organs could have different effects on the crop spectral features (Li et al, 2015(Li et al, , 2021. However, few investigations under field conditions address the differences of estimated the NC in different organs when using UAV-based multispectral data.…”
Section: Introductionmentioning
confidence: 99%